Numerical investigation of dual‐source gas explosion dynamics in h‐type tunnels under varied enclosed situations - Weijian Wang; Qing Ye; Zhenzhen Jia (Energy Science & Engineering)
Abstract To further investigate the propagation characteristics of shock waves and flame waves in H‐type tunnel gas explosions, numerical simulation studies were conducted on a dual‐source gas explosion model using Fluent software. Three distinct operational conditions were designed and modeled, leading to the following outcomes. The shock wave flow field parameters from dual sources (with equal source energy) are symmetrically distributed in the H‐type tunnel, with high pressure and low flow velocity in the connecting roadway between the two shock waves. Under different conditions, the pressure is generally higher in closed tunnels (fully closed greater than semi‐closed) and lower in open tunnels. The largest overpressure in non‐explosion areas occurs at the closed ends and in the connecting roadway, while the areas bearing the greatest impulse are the shock wave reflection zones and pressure coupling regions. In closed conditions, the flame wave first moves forward and then propagates backward after the explosion, influenced by reflected waves and pressure differences between the ends and the tunnel. In open conditions, the pressure in the flame zone is lower than at both ends, inhibiting the forward propagation of the flame wave.